Evaluasi Sistem Pelaporan Kekerasan Seksual di Perguruan Tinggi: Pendekatan Black-Box dan Kepatuhan terhadap Permendikbudristek No. 30/2021 - Nursetia Wati; Mohidin, Ismail; Hermawanto, Fajar; Suleman, Salman (Universitas Negeri Gorontalo, 2025)
The sexual violence reporting system is a critical component in creating a safe and responsive campus environment for victims. This study aims to evaluate a web-based sexual violence reporting system implemented at a higher education institution by integrating Black-Box Testing and Compliance Testing approaches. The evaluation assesses both the system’s functional performance from a user perspective and its adherence to relevant regulations, particularly Permendikbudristek No. 30 of 2021. The results of Black-Box Testing indicate that most features function properly, although some issues were found in error messaging and the usability of anonymous reporting options. Meanwhile, Compliance Testing shows that the system fulfills most regulatory indicators, but there are still weaknesses in access control to victim data by internal staff. These findings highlight the importance of comprehensive evaluation in systems dealing with sensitive issues to ensure both technical reliability and compliance with principles of justice and victim protection.